Metal Leaching and Reductive Dissolution of Iron from Contaminated Soil and Sediment Samples by Indigenous Bacteria and Bacillus Isolates. Issue 5 (3rd July 2016) - Štyriaková, Iveta; Štyriak, Igor; Balestrazzi, Alma; Calvio, Cinzia; Faè, Matteo; Štyriaková, Darina
ABSTRACT: The purpose of this study was to leach Cu, Zn, As, and Fe from contaminated soil and sediment samples with indigenous heterotrophic bacteria isolated from the study sites. The sediment contained Fe in the form of goethite and low concentrations of other metals. The soil contained hematite and high concentrations of other metals. The environmental conditions affected the bacterial activity in the metals dissolution. As and Fe were the major metals leached from the sediment sample while a minor fraction of Cu was solubilized. Cu and Zn were the major metals leached from the soil sample while only a minor fraction of Fe was dissolved. As a control, a disinfectant was used for partial inactivation of indigenous bacteria. This treatment had a negative effect on the leaching of Fe, Zn and As from soil and sediment samples, but it increased Cu dissolution from the sediment. Bacterial different dissolution of Fe during soil and sediment bioleaching was also investigated with ferrihydrite. The iron concentration was much higher during ferrihydrite dissolution when indigenous bacteria from sediment were used compared to indigenous bacteria isolated from soil. The indigenous bacterial inoculum provided more biological and metabolic diversity which may account for the difference in reductive iron reduction from ferrihydrite. The Bacillus cultures isolated from soil and sediment samples showed similar efficiencies in reductive dissolution of ferrihydrite. The synergetic bacterial inhibition effect created by the environmental conditions can influence bioremediation effect.